Sosialisasi Pola Asuh Positif sebagai Upaya Pembentukan Karakter Anak di Lingkungan Desa Ngadirejo - Sulthoni Putra Rofiqi, Alif Ahmad; Karomah, Alfi; Auliya Afifah, Fathia; Choirunnia, Alya; Hidayati, Nurul; Adenanty, Annisa (Jurnal Makkareso, 2025)
This article discusses the importance of socialization of parenting patterns in the formation of children's character in Ngadirejo Village, Jabung District, Malang Regency. This study aims to improve parents' understanding of appropriate parenting patterns and their impact on children's character development. The methods used in this socialization include lectures and discussions involving parents of students at Dharma Wanita Kindergarten. The results of the activity showed that community enthusiasm was very high, with many parents actively participating in the question and answer session and discussing the material presented. This activity succeeded in raising awareness of the importance of positive parenting patterns, which can support children's physical, emotional, and intellectual development. With this socialization, it is hoped that parents can apply good parenting principles, so that children can grow into individuals with character and are able to adapt well in society..